Good Jobs, Bad Jobs: What's Trade Got To Do With It? - James Lake; Daniel L. Millimet (Institute for the Study of Labor (IZA), 2016)
Using US local labor markets between 1990 and 2010, we analyze the heterogeneous impact of rising trade exposure on employment growth of 'good' and 'bad' jobs. Three salient findings emerge. First, rising local exposure to import competition, via falling US tariffs or rising Chinese import penetration, reduces (increases) employment growth of bad (good) jobs. Conversely, improved local access to export markets, via falling foreign tariffs, increases (reduces) employment growth of bad (good) jobs. Second, falling US tariff protection is substantially more important, economically and statistically, than rising Chinese import penetration. Third, globalization generates occupational polarization but not job polarization.
Keywords: F13; J21; J31; 330; trade liberalization; China; local labor markets; job polarization; occupational polarization